2019
DOI: 10.1242/dev.163428
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human placenta

Abstract: The placenta is essential for normal in utero development in mammals. In humans, defective placental formation underpins common pregnancy disorders such as pre-eclampsia and fetal growth restriction. The great variation in placental types across mammals means that animal models have been of limited use in understanding human placental development. However, new tools for studying human placental development, including 3D organoids, stem cell culture systems and single cell RNA sequencing, have brought new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
433
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(445 citation statements)
references
References 208 publications
(232 reference statements)
4
433
0
8
Order By: Relevance
“…The second study of human placenta confirmed the result and showed increasing expression of ACE2 in EVT at 24 week. The major function of the placenta is performed by trophoblast cells including VCT, SCT and EVT [22]. The SCT is the outer lining of the placental villi which has direct contact with maternal blood flowing into the intervillous space which also plays as the main site of maternal and fetal exchange [23].…”
mentioning
confidence: 99%
“…The second study of human placenta confirmed the result and showed increasing expression of ACE2 in EVT at 24 week. The major function of the placenta is performed by trophoblast cells including VCT, SCT and EVT [22]. The SCT is the outer lining of the placental villi which has direct contact with maternal blood flowing into the intervillous space which also plays as the main site of maternal and fetal exchange [23].…”
mentioning
confidence: 99%
“…By contrast, studies in mouse are highlighting the complex developmental dynamics of the mouse TE lineage during implantation and gastrulation [130]. The comparative analysis of these datasets will surely contribute to a better understanding of the transcriptional factors, signaling pathways, and extracellular environment that may be necessary to maintain the population of human TE cells in culture as bona fide TSCs [131].…”
Section: Stem Cells For Human Placental Development and Organoidsmentioning
confidence: 99%
“…In addition, the development of 3D organoid models using human placental tissue and endometrial tissue has also been attempted and shows promising clinical relevance in the study of pregnancy-related diseases [13,131]. Organoids are small aggregates of cells that originate from a single (or very few) cells, either pluripotent stem cells or organ progenitors, and that can grow and self-organize into a 3D structure that recapitulates a specific function of a specific organ (of origin).…”
Section: Stem Cells For Human Placental Development and Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para muchos analistas la simpatía es, tal vez, el elemento fundamental en la ética de Smith, proveniente de Hume 87 . Sin embargo, nosotros no hemos profundizado en ella porque creemos que la simpatía, pese a su importancia innegable, fue para Smith algo derivado, una de las consecuencias no planificadas de la dialógica de la interacción lingüística, que nos obliga a ponernos en el lugar del otro y al otro a ponerse en el nuestro.…”
Section: La Comunicación Teatralizadaunclassified